Sustainable Destination Development through Community Based Tourism at Bul-Bul Beach Tourism Object, Toba Regency - Asmah Kartika Dalimunthe (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2021)
This study identifies that in the development of a tourism destination in an area it is inseparable from the relationship between managers, stakeholders and the community, the Bulbul Beach tourist area in Toba Regency is a tourist destination that has the potential to continue to be developed because of the potential attractions in the Bulbul Beach area. The method used in qualitative descriptive research which is sourced from secondary data by conducting field studies and collecting data in the field and observation. This study concludes that developing a sustainable destination must be accompanied by the readiness of the actors, the community and workers in terms of tourism training so that there are no obstacles that hinder the development process due to the lack of readiness on the part of managers, communities and employees about tourism knowledge.